492 Periprocedural Polypharmacy in Lumbar Fusions Performed Under Spinal Anesthesia Compared to General Anesthesia. (April 2023) - Olmos, Michelle; Hernandez, Nicholas; Kanter, Matthew; Liu, Penny; Riesenburger, Ron I.; Kryzanski, James
Abstract : INTRODUCTION: Lumbar spinal surgery is most often performed under general endotracheal anesthesia (GEA), however spinal anesthesia (SA) is a safe and effective alternative. Postoperative cognitive dysfunction (POCD) is a complication of GEA and the risk of POCD is associated with anesthetic modality and perioperative polypharmacy. Despite the many benefits of SA described in the literature, its efficacy in decreasing polypharmacy has not yet been determined. METHODS: Demographic and procedural data of 424 patients undergoing single TLIF via GEA (n = 186) and SA (n = 238) were extracted from our institution's electronic medical record. We investigated perioperative medication types, number of intraoperative hypotensive episodes, vasopressor requirement, and overall number of perioperative medications used between the two patient groups. RESULTS: The number of perioperative medications differed significantly between the two cohorts with the SA cohort receiving a mean of 4.5 medications and the GEA cohort receiving a mean of 10.5 medications (p < 0.0001).This reduction in perioperative medications remained significant after a multivariable analysis to control for confounders (p < 0.001 for all variables). Use of vasopressors was significantly reduced in the SA cohort (p < 0.001), which coincided with a significant reduction in hypotensive episodes in the SA cohort (p < 0.001). Patients undergoing TLIF via GEA had 3.6 times greater odds of experiencing a hypotensive episode intraoperatively (OR = 3.62, 95% CI [2.38-5.49]). CONCLUSIONS: Spinal anesthesia is associated with a significant decrease in perioperative medications, including lower vasopressor requirements. We postulate that SA may confer superior intraoperative hemodynamic stability which lowers pressor requirements. The decrease of perioperative medications may be an important contribution in reducing the incidence of POCD in patients undergoing TLIFs.